EPH Receptor B4 (EPHB4) Gene Polymorphisms and Risk of Intracranial Hemorrhage in Patients with Brain Arteriovenous Malformations - Weinsheimer, Shantel (2009)
BACKGROUND: Brain arteriovenous malformations (BAVM) are a tangle of abnormal vessels directly shunting blood from the arterial to venous circulation and an important cause of intracranial hemorrhage (ICH). EphB4 is involved in arterial-venous determination during embryogenesis; altered signaling could lead to vascular instability resulting in ICH. We investigated the association of single-nucleotide polymorphisms (SNPs) and haplotypes in EPHB4 with risk of ICH at clinical presentation in BAVM patients. METHODS AND RESULTS: Eight haplotype-tagging SNPs spanning ∼29 kb were tested for association with ICH presentation in 146 Caucasian BAVM patients (phase I: 56 ICH, 90 non-ICH) using allelic, haplotypic, and principal components analysis. Associated SNPs were then genotyped in 102 additional cases (phase II: 37 ICH, 65 non-ICH) and data combined for multivariable logistic regression. Minor alleles of 2 SNPs were associated with reduced risk of ICH presentation (rs314313 C, P=0.005; rs314308 T, P=0.0004). Overall, haplotypes were also significantly associated with ICH presentation (χ(2)=17.24, 6 df, P=0.008); 2 haplotypes containing the rs314308 T allele (GCCTGGGT, P=0.003; GTCTGGGC, P=0.036) were associated with reduced risk. In principal components analysis, 2 components explained 91% of the variance, and complemented haplotype results by implicating 4 SNPs at the 5′ end, including rs314308 and rs314313. These 2 SNPs were replicated in the phase II cohort, and combined data resulted in greater significance (rs314313, P=0.0007; rs314308, P=0.00008). SNP association with ICH presentation persisted after adjusting for age, sex, BAVM size, and deep venous drainage. CONCLUSIONS: EPHB4 polymorphisms are associated with risk of ICH presentation in BAVM patients, warranting further study.